Application of few-layer WSe2/Sapphire in passively Q-switched solid-state lasers as saturable absorber and output coupler. (July 2019) - Yang, Jingnan; Dou, Xiaodan; Ma, Yanjun; Tian, Kan; Li, Yuhang; Xu, Honghao; Han, Wenjuan; Liu, Junhai
Highlights: A microchip Yb:LuPO4 /WSe2 passively Q-switched laser is demonstrated. Sapphire substrate of WSe2 film is used as an etalon output coupler. An output power of 1.8 W at 1.2 MHz is generated with pulse duration of 30 ns. Abstract: We demonstrate that it is possible for a few-layer WSe2 /Sapphire to act in specific high-gain solid-state lasers as both saturable absorber for passive Q-switching and as etalon mirror for output coupling. A passively Q-switched Yb:LuPO4 microchip laser formed in this manner is realized. With 11.5 W of pump power absorbed, a maximum output power of 1.8 W is produced at a pulse repetition rate of 1.2 MHz with a slope efficiency of 25%; the resulting pulse energy, duration, and peak power are, respectively, 1.5 μJ, 30 ns, and 50 W. Our work provides a simple way of making compact, reliable, high-repetition-rate pulsed microchip or miniature solid-state lasers based on 2D saturable absorbers.